2000
DOI: 10.1038/sj.ijo.0801405
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a children's summer camp programme on weight loss, with a 10 month follow-up

Abstract: OBJECTIVE: To assess the long-term effects of a multidisciplinary approach involving structured fun-type skill learning physical activities in the treatment of obese and overweight children. DESIGN: A longitudinal investigation incorporating repeated measurements before and after the 8 week intervention and after the 44 week follow-up period. METHODS: The camp programme (Massachusetts, USA) utilised structured fun-based skill learning physical activities, moderate dietary restriction and behaviour modi®cation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
2
7

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 38 publications
5
71
2
7
Order By: Relevance
“…16 Our data are consistent with the results from previous studies using exercise combined with a balanced diet. 8,9,[23][24][25][26][27] Caloric restriction may induce negative side effects such as growth retardation. Therefore, a weight loss program in obese children and adolescents must pay attention to ensure lasting growth and development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Our data are consistent with the results from previous studies using exercise combined with a balanced diet. 8,9,[23][24][25][26][27] Caloric restriction may induce negative side effects such as growth retardation. Therefore, a weight loss program in obese children and adolescents must pay attention to ensure lasting growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…As such a multidisciplinary approach proves to be difficult to reach in the usual environment, in-patient units have been designed to help adolescents suffering the most severe forms of obesity. 7,8 Managing weight loss in obese adolescents actually requires paying special attention to potential negative side effects since several studies reported a lost of lean body mass following a low-calorie diet. 9 The dual-energy X-ray absorptiometry (DEXA) has been validated as an efficient tool to assess the total and regional body composition in vivo, 10 in adults 11 and in children.…”
Section: Introductionmentioning
confidence: 99%
“…Previous outcome data on the effectiveness of a US-based 8-week programme showed that it was successful in producing significant decreases in BMI and overall body fat. 23 These researchers found that although participants regained some of the weight lost, BMI increase was not statistically significant and did not produce a return to initial mean levels. At 1-y follow-up, BMI remained significantly lower than at the beginning of the intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Treatments typically aim to support changes in lifestyle, with the most successful tending to include exercise, diet and behavioural components(3) Community-based treatments are typically a first-line measure, but extent of weight-loss is often relatively small(3); residential weight management camps provide an alternative, more intensive intervention to support children to change their lifestyle to achieve a healthier body weight (4,5). Weight-management camps tend to induce greater weight loss than community interventions (4), but studies have revealed considerable between-subject variability in extent of long-term post-intervention weight management success (6). This may be partly explained by variation between attendees' levels of impulsivity.…”
Section: Introductionmentioning
confidence: 99%